Activation of human B cells negatively regulates TGF-β1 production. Issue 1 (December 2017) - Molnarfi, Nicolas; Bjarnadóttir, Kristbjörg; Benkhoucha, Mahdia; Juillard, Catherine; Lalive, Patrice
Abstract Background Accumulating evidence indicate that B cells can exhibit pro- or anti-inflammatory activities. Similar to interleukin (IL)-10–competent B cells, we recently showed that transforming growth factor (TGF)-β1-producing regulatory B cells limit the induction of autoimmune neuroinflammation in mice, making them potentially important in maintaining peripheral immune tolerance in central nervous system inflammatory demyelinating disorders such as multiple sclerosis. Methods In this study, we compared B cell production of TGF-β1 and IL-10, the two most studied regulatory cytokines, and the pro-inflammatory B cell-derived IL-6 and tumor necrosis factor cytokines under basal conditions and following polyclonal stimulation with dual B cell receptor (BCR) cross-linking and Toll-like receptor (TLR)9 engagement. Results We showed that resting TGF-β1–producing B cells fall within both the naïve (CD27− ) and memory (CD27+ ) B cell compartments. We found no spontaneous B cell-derived IL-10, IL-6 or tumor necrosis factor (TNF) production. Human B cell activation with anti-Ig antibodies plus CPG-B leads to only modest IL-10 production by memory CD19+ CD27+ B cells while expression levels of IL-6 and TNF by both naive and memory B cells were strongly induced. Remarkably, stimulated B cells showed significantly reduced capacity to produce TGF-β1. Conclusions These findings indicate that B cell activation may facilitate the development of excessive immune responses and autoimmunity by restricting B cell-derived TGF-β1 production by resting B cells and favoring in turns the proinflammatory actions of activated cytokine-producing B cells.